Uji Toksisitas Akut, Aktivitas Antioksidan In Vitro dan Efek Rebusan Bunga Kemboja Merah (Plumeria rubra L.) terhadap Kadar Malondialdehid - NI MADE DWI SANDHIUTAMI; LESTARI RAHAYU (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Antioxidants are substances that may inhibit free radical reactions in the body. The purpose of this research is to identify lethal dose, in vitro antioxidant activity and effect of kemboja merah flowers decoction (Plumeria rubra L.) on MDA level. Lethal dose was measured by Weil method. Antioxidant activity assays was performed in vitro by DPPH method and in vivo by measuring MDA plasma level. The level of MDA was conducted using the thiobarbituric acid reactivity test. In the test, 30 mices were divided into 6 groups: normal, negative control, positive control and 3 group treated with variation dose of kemboja merah flowers decoction. LD50 of decoction kemboja merah flowers is > 15 g/kg of body weight. In vitro, antioxidant activity showed the IC50 value of decoction kemboja merah flowers is 36.96 μg/mL.The antioxidant activity of decoction kemboja merah flowers is smaller than vitamin C (IC50 5.89 μg/mL). In vivo antioxidant activity showed levels of MDA on normal group is 1.66 nmol/mL, negative control group is 5.67 nmol/mL, positive control group is 1.45 nmol/mL, treated group which was given by decoction kemboja merah flowers at dose 0.39 g/kg of body weight is 4.32